Students’ Strategies and Self-Efficacy in Reading Comprehension - Sri Fatta Meldawati; Aida Hanim A Hamid (Naifaderu Cipta Sejahtera, 2023)
Purpose This study aims to contribute theoretically and practically. Theoretically, this study provides new insights into reading strategies, self-efficacy, and reading comprehension. In addition, it is expected to be used as information for students in choosing the right reading strategy to complete the task at schools. Practically, the analysis presented in this study provides valuable information for future research exploring students' reading strategies and self-efficacy. Methodology This type of research is qualitative research in nature. This method aims to describe the phenomena related to the topic of this study. The researcher used purposive sampling technique. Data were obtained through observations and interviews of second semester students who took literal reading courses and who had high grades in the first semester. Results/Findings The results showed that the undergraduate EFL students in a public university used cognitive strategies, compensatory strategies and social strategies. These undergraduate students’ reading strategies can affect reading comprehension based on the results of observations, self-efficacy affects reading comprehension. The interview results show that reading strategies used by the students in this study affect their English improvement in terms of English comprehension. Students have high self-efficacy in comprehending different English texts. Implications The evidence of this study identifies that it is very important to apply strategies that are appropriate to the characteristics of students especially those that encourage students' self-efficacy in learning. With high self-efficacy, students can improve their reading comprehension. Lecturers and teachers can also consider it as a reference in teaching reading strategies in class and student efficacy.